Visible common bile duct at the duodenum due to the destructive effect of the tumor - Erkin ÖZTAŞ,; Erkan PARLAK,; Abdurrahim SAYILIR,; Ülkü DAĞLI,; Mehmet ARHAN,; Diğdem ETİK,; Aysel ÜLKER, (Turkish Journal of Gastroenterology, 2019)
-